Habitat‐dependent occupancy and movement in a migrant songbird highlights the importance of mangroves and forested lagoons in Panama and Colombia. Issue 19 (26th September 2019) - Bulluck, Lesley; Ames, Elizabeth; Bayly, Nicholas; Reese, Jessie; Viverette, Cathy; Wright, James; Caguazango, Angela; Tonra, Christopher
Abstract: Climate change is predicted to impact tropical mangrove forests due to decreased rainfall, sea‐level rise, and increased seasonality of flooding. Such changes are likely to influence habitat quality for migratory songbirds occupying mangrove wetlands during the tropical dry season. Overwintering habitat quality is known to be associated with fitness in migratory songbirds, yet studies have focused primarily on territorial species. Little is known about the ecology of nonterritorial species that may display more complex movement patterns within and among habitats of differing quality. In this study, we assess within‐season survival and movement at two spatio‐temporal scales of a nonterritorial overwintering bird, the prothonotary warbler ( Protonotaria citrea ), that depends on mangroves and tropical lowland forests. Specifically, we (a) estimated within‐patch survival and persistence over a six‐week period using radio‐tagged birds in central Panama and (b) modeled abundance and occupancy dynamics at survey points throughout eastern Panama and northern Colombia as the dry season progressed. We found that site persistence was highest in mangroves; however, the probability of survival did not differ among habitats. The probability of warbler occupancy increased with canopy cover, and wet habitats were least likely to experience local extinction as the dry season progressed. We also found that warbler abundance is highest in forests with the tallest canopies. This study is one of the first to demonstrate habitat‐dependent occupancy and movement in a nonterritorial overwintering migrant songbird, and our findings highlight the need to conserve intact, mature mangrove, and lowland forests. Abstract : We found that overwintering occupancy and movement are habitat‐dependent in a nonterritorial overwintering migrant bird. Warblers in mangroves and other wet habitats are least likely to experience local extinction as dry season progresses, and warbler abundance was highest in mature mangroves forests. Conserving mangroves and forested wetlands is key to retaining quality winter habitat for migratory birds.